Progressive Quadrature Rules for Approximate Evaluation of Real Definite Integrals - et al., 1Biranchi Narayan Dash (International Journal of Advanced Science and Technology, 2019)
A class of progressive quadrature rules for the approximate evaluation  of real definite integrals has been proposed in this paper.  Rules have been examined with standard test integrals  and their respective error bounds  have been determined.